Síntese e caracterização de hidrogéis à base de goma guar oxidada e gelatina - Canafístula, Francisca Vanessa Carneiro (2020)
Hydrogels can be defined as three-dimensionally reticulated networks, which absorb and retain water and/or biological fluids without dissolving. This class of materials has several characteristics such as: similarity to the extracellular tissue matrix (ECM) and support for cell growth and nutrient transport, increasing cell viability and proliferation. These properties allow its use in several biomedical applications, including tissue engineering, wound dressings and drug administration. Hydrogels obtained via cross-linking by Schiff's base reaction prepared from natural polymers have gained special attention, since they have biodegradability and biocompatibility. In this sense, the objective of this work was to synthesize hydrogels based on oxidized guar gum (GGOX) and gelatin (GELP) via cross-linking by Schiff's base reaction, aiming at the application as wounds dressings. Guar gum (GG) was depolymerized in order to increase solubility, oxidized with sodium periodate in different degrees of oxidation (20, 50 and 80%) and characterized by FTIR, NMR, GPC, TG and rheology. The change was confirmed by FTIR and NMR. The GPC chromatograms of GG and oxidized derivatives show that the peak molar mass (Mpk) decreases with increasing GG oxidation. Hydrogels were prepared by mixing their precursors (GGOX and GELP), in different volume/volume (v/v) ratios of GGOX/GELP (20:80, 30:70 and 40:60). The hydrogels were characterized by gelation time, FTIR, rheology, TG, SEM, swelling and degradation. The crosslinking reaction of the hydrogels was confirmed by FTIR. The gelation time (Tgel) was dependent on the degree of oxidation and on the GGOX/GELP ratio. The gelation was efficient, since it improved the mechanical and morphological properties of these materials. The GGOX80/GELP hydrogels showed good mechanical properties, swelling rate and adequate degradation time to act as candidates for future biomedical applications in the field of dressings and/or tissue engineering.